Optimising Large Animal Models of Sustained Atrial Fibrillation: Relevance of the Critical Mass Hypothesis - Denham, Nathan C.; Pearman, Charles M.; Madders, George W. P.; Smith, Charlotte E. R.; Trafford, Andrew W.; Dibb, Katharine M. (Frontiers in Physiology, 2021)
Background: Large animal models play an important role in our understanding of the pathophysiology of atrial fibrillation (AF). Our aim was to determine whether prospectively collected baseline variables could predict the development of sustained AF in sheep, thereby reducing the number of animals required in future studies. Our hypothesis was that the relationship between atrial dimensions, refractory periods and conduction velocity (otherwise known as the critical mass hypothesis) could be used for the first time to predict the development of sustained AF. Methods: Healthy adult Welsh mountain sheep underwent a baseline electrophysiology study followed by implantation of a neurostimulator connected via an endocardial pacing lead to the right atrial appendage. The device was programmed to deliver intermittent 50Hz bursts of thirty seconds duration over an eight-week period whilst sheep were monitored for AF. Results: Eighteen sheep completed the protocol, of which 28% developed sustained AF. Logistic regression analysis showed only fibrillation number (calculated using the critical mass hypothesis as the left atrial diameter divided by the product of atrial conduction velocity and effective refractory period) was associated with an increased likelihood of developing sustained AF (Ln Odds Ratio 26.1 [95% confidence intervals 0.2-52.0] p=0.048). A receiver-operator characteristic curve showed this could be used to predict which sheep developed sustained AF (C-statistic 0.82 [95% confidence intervals 0.59-1.04] p=0.04). Conclusion: The critical mass hypothesis can be used to predict sustained AF in a tachypaced ovine model. These findings can be used to optimise the design of future studies involving large animals.